2019
DOI: 10.1017/jfm.2019.702
|View full text |Cite
|
Sign up to set email alerts
|

Reattachment streaks in hypersonic compression ramp flow: an input–output analysis

Abstract: We employ global input-output analysis to quantify amplification of exogenous disturbances in compressible boundary layer flows. Using the spatial structure of the dominant response to time-periodic inputs, we explain the origin of steady reattachment streaks in a hypersonic flow over a compression ramp. Our analysis of the laminar shock/boundary layer interaction reveals that the streaks arise from a preferential amplification of upstream counter-rotating vortical perturbations with a specific spanwise wavele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 48 publications
10
76
0
Order By: Relevance
“…This trend is reminiscent of the various flow structures resulting from the eigenvalue decomposition of the steady-state covariance matrix (cf. Section IV) and has been also recently observed in spatio-temporal analysis of hypersonic boundary layer flows [60].…”
Section: B Frequency Response Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…This trend is reminiscent of the various flow structures resulting from the eigenvalue decomposition of the steady-state covariance matrix (cf. Section IV) and has been also recently observed in spatio-temporal analysis of hypersonic boundary layer flows [60].…”
Section: B Frequency Response Analysismentioning
confidence: 62%
“…Previously, tools from sparse linear algebra in conjunction with iterative schemes have been employed to analyze the eigenspectrum of the governing equations and provide insight into the dynamics of transitional flows [50][51][52][53][54]. Efforts have also been made to conduct non-modal analysis of spatially evolving flows including transient growth [55,56] and resolvent [57][58][59][60] analyses. In particular, for the flat-plate boundary layer flow, the sensitivity of singular values of the resolvent operator to base-flow modifications and subsequent effects on the TS instability mechanism and streak amplification was investigated in [57].…”
Section: Introductionmentioning
confidence: 99%
“…Yet it did not discuss from a physical viewpoint the nature of the linear amplification mechanism of streaks, which plays a central role in the overall dynamics of the flow. Even if good candidates for the linear amplification of longitudinal structures would be the centrifugal effect linked to Görtler instabilities (Navarro-Martinez & Tutty 2005;Benay et al 2006;Murray et al 2013) or the lift-up effect such as pointed out by Bugeat et al (2019) (albeit only for boundary layer flow), a recent study by Dwivedi et al (2019) tends to show that they are due to baroclinic effects. The work of Dwivedi et al (2019) focuses on a laminar flow and does not address directly the question of transition, but nonetheless, it provides insights about the amplification mechanism of so-called 'reattachment vortices' in an hypersonic compression ramp flow.…”
Section: Proposed Scenario For the Transition Processmentioning
confidence: 99%
“…However, the mechanism proposed by Görtler (1940) is not the only one that can lead to the amplification of steady vortices. For instance, Dwivedi et al (2019) showed that a baroclinic mechanism could also lead to the growth of such structures. Another possible mechanism would be the 'lift-up' effect such as pointed out by the work of Bugeat et al (2019) (albeit for an attached boundary layer only).…”
Section: Introductionmentioning
confidence: 99%
“…2. Turbulence modeling for complex fluids and flows in complex geometries (101,102,103,104,105,106,107,108) requires dealing with a large number of degrees of freedom. Since improving upon current algorithms that require O(n 3 ) computations for a model with n states is challenging, a possible direction is to examine physical approximations (109,110,111,112) and model reduction techniques (13,15,16,17).…”
Section: Future Issuesmentioning
confidence: 99%